Haematological issues in neonates with neonatal encephalopathy treated with hypothermia. Issue 4 (August 2021) - Isweisi, Eman; Moore, Carmel Maria; Hurley, Tim; Sola-Visner, Martha; McCallion, Naomi; Ainle, Fionnuala Ni; Zareen, Zunera; Sweetman, Deirdre U.; Curley, Anna E.; Molloy, Eleanor J.; ,
Abstract: Neonatal encephalopathy (NE) is associated with abnormality of neurological function and involves multiorgan dysfunction. There are long-term complications such as cerebral palsy and developmental delay. Cardiac, renal, neurological and other organ dysfunctions are well described. Haematological dysfunction is relatively common and includes anaemia, thrombocytopenia, monocyte and neutrophil activation, hypofibrinogenemia and coagulopathy. There is a lack of consensus definitions of hematological parameters and optimal levels for intervention due to the lack of interventional studies in term neonates and the lack of knowledge of the optimal values during therapeutic hypothermia. However, derangements in hematological values are also associated with neurodevelopmental outcomes. This article outlines the different hematological complications associated with NE and therapeutic hypothermia and suggests a framework for management.